2000
DOI: 10.1017/s1368980000000562
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of St. John's wort for the treatment of major depression

Abstract: Objective: Extracts of St. John's wort have been widely used in the treatment of depression. Our aim was to review information related to the efficacy and safety of St. John's wort as an antidepressant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Here, hyperforin pharmacokinetics was linear for doses up to 600 mg whereas higher doses produced lower-than-expected plasma concentrations after linear extrapolation. In a study employing repeated doses, hyperforin accumulation was not be detected; steadystate plasma concentration after 900 mg/day of extract was~100 ng/ml (Biber et al, 1998) with a half-life of 9 h (Nangia et al, 2000) (Table 2).…”
Section: Pharmacodynamics and Pharmacokinetics Of Hypericum Perforatummentioning
confidence: 99%
See 1 more Smart Citation
“…Here, hyperforin pharmacokinetics was linear for doses up to 600 mg whereas higher doses produced lower-than-expected plasma concentrations after linear extrapolation. In a study employing repeated doses, hyperforin accumulation was not be detected; steadystate plasma concentration after 900 mg/day of extract was~100 ng/ml (Biber et al, 1998) with a half-life of 9 h (Nangia et al, 2000) (Table 2).…”
Section: Pharmacodynamics and Pharmacokinetics Of Hypericum Perforatummentioning
confidence: 99%
“…After oral administration of single doses (range = 300–1800 mg ) of HP extract (0.3% of hypericin), hypericin was detectable in the blood after 1.3 h, and peak plasma concentrations were reached after ~4.6 h and steady‐state levels by 4 days (Brochmoller et al ., ; Staffeldt et al ., 1994; Upton, ). The plasma half‐life of hypericin is reported to be ~25 h (Nangia et al ., ), the prolonged duration of which is due to hypericin's affinity for albumin and lipoproteins (Bianchi et al ., ). Although the bioavailability of hypericin is ~14%, the therapeutic concentration of hypericin in brain remains unknown, and although it has been suggested that brain levels reach only 5% of plasma levels, hypericin's half‐life in the brain may be weeks (Upton, ).…”
Section: Pharmacodynamics and Pharmacokinetics Of Hypericum Perforatummentioning
confidence: 99%
“…The antidepressant effects of SJW have been the focus of a number of controlled clinical studies that have been extensively reviewed [7,19,[24][25][26][27]. However, the mechanism(s) by which SJW exerts antidepressive effects in human subjects across certain types of depression remain to be elucidated.…”
Section: Effects Of St John's Wort On Depressionmentioning
confidence: 99%
“…Hypericin remains intact through digestion, absorption into the blood stream, and passage through the liver, and is felt to be able to cross the blood-brain barrier, 13 with effects originally thought to be mediated through irreversible inhibition of monoamine oxidase (MAO). 14 However, these findings were not replicated and subsequent work has raised doubts as to the importance of hypericin as the primary active ingredient of hypericum.…”
Section: Chemical Constituentsmentioning
confidence: 99%